2021
DOI: 10.1007/s00729-021-00167-4
|View full text |Cite
|
Sign up to set email alerts
|

Disziplin, Profession und evidenzbasierte Praxis: Zur Stellung der Psychotherapie im Gesundheitssystem. Eine Bilanz

Abstract: Zusammenfassung30 Jahre nach der Verabschiedung des österreichischen Psychotherapiegesetzes wird die Besonderheit der Psychotherapie im Gesundheitssystem mit Bezug auf nationale Gegebenheiten und international vorliegende Forschungsergebnisse dargestellt. Dabei werden zentrale Qualitäts- und Unterscheidungsmerkmale der Psychotherapie im Verhältnis zur Klinischen Psychologie und zu weiteren Gesundheitsberufen unter Miteinbeziehung von evidenzbasierter Forschungsliteratur vorgestellt. Es wird deutlich gemacht, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Professional education for psychotherapists in Austria is subject to the Psychotherapy Act. Aspiring psychotherapists must be particularly motivated to practice their job since, in contrast to other legally recognized health professions, the training must be entirely funded by the candidates ( 48 ). It is extended over an average of 8.9 years ( 49 ) and somewhat selective through admission procedures to the specialized training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional education for psychotherapists in Austria is subject to the Psychotherapy Act. Aspiring psychotherapists must be particularly motivated to practice their job since, in contrast to other legally recognized health professions, the training must be entirely funded by the candidates ( 48 ). It is extended over an average of 8.9 years ( 49 ) and somewhat selective through admission procedures to the specialized training.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the curricula prescribe a high number of hours of self-experience or teaching therapy. This structure is supposed to select only candidates with higher reflective competence to remain in the process ( 48 ). Research has shown that improved reflective ability is associated with systematic attempts to develop it, a safe atmosphere, peer support and time to reflect ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in Germany or Switzerland, it is not necessary to have a degree in psychology to complete psychotherapy training; it is even possible to become a psychotherapist without a degree in Austria ( Bundesrepublik Österreich, 1990 ). This is expected to change in the next few years, as a new psychotherapy law is currently being prepared and is expected to be submitted for parliamentary review in the second half of 2023 ( Datler et al, 2023 ).…”
Section: Psychotherapeutic Education In German-speaking Countries Wit...mentioning
confidence: 99%